Callosal agenesis and congenital mirror movements: outcomes associated with DCC mutations. (14th February 2020) - Spencer‐Smith, Megan; Knight, Jacquelyn L; Lacaze, Emmanuelle; ,; Depienne, Christel; Lockhart, Paul J; Richards, Linda J; Heron, Delphine; Leventer, Richard J; Robinson, Gail A
Abstract : Pathogenic variants in the gene encoding deleted in colorectal cancer ( DCC ) are the first genetic cause of isolated agenesis of the corpus callosum (ACC). Here we present the detailed neurological, brain magnetic resonance imaging (MRI), and neuropsychological characteristics of 12 individuals from three families with pathogenic variants in DCC (aged 8–50y), who showed ACC and mirror movements ( n =5), mirror movements only ( n =2), ACC only ( n =3), or neither ACC nor mirror movements ( n =2). There was heterogeneity in the neurological and neuroimaging features on brain MRI, and performance across neuropsychological domains ranged from extremely low (impaired) to within normal limits (average). Our findings show that ACC and/or mirror movements are associated with low functioning in select neuropsychological domains and a DCC pathogenic variant alone is not sufficient to explain the disability. What this paper adds: Neuropsychological impairment severity is related to presence of mirror movements and/or agenesis of the corpus callosum. A DCC pathogenic variant in isolation is associated with the best prognosis. What this paper adds: Neuropsychological impairment severity is related to presence of mirror movements and/or agenesis of the corpus callosum. A DCC pathogenic variant in isolation is associated with the best prognosis. This article is commented on by Franz on page 669 of this issue. Video Podcast: https://youtu.be/0HFp9RtIM8U